2010
DOI: 10.3945/jn.110.123414
|View full text |Cite
|
Sign up to set email alerts
|

Simple Food Group Diversity Indicators Predict Micronutrient Adequacy of Women’s Diets in 5 Diverse, Resource-Poor Settings

Abstract: Women of reproductive age living in resource-poor settings are at high risk of inadequate micronutrient intakes when diets lack diversity and are dominated by staple foods. Yet comparative information on diet quality is scarce and quantitative data on nutrient intakes is expensive and difficult to gather. We assessed the potential of simple indicators of dietary diversity, such as could be generated from large household surveys, to serve as proxy indicators of micronutrient adequacy for population-level assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
540
4
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 522 publications
(585 citation statements)
references
References 28 publications
31
540
4
10
Order By: Relevance
“…Our eight-food-group system shared a number of similarities to the recently recommended nine-food-group system also known as the Women's Dietary Diversity Score (WDDS) and the seven-group young children's (6 to 23 months old) DDS (12,23,24) . All three systems have specific food groups for cereals and tubers, dairy products and legumes and nuts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our eight-food-group system shared a number of similarities to the recently recommended nine-food-group system also known as the Women's Dietary Diversity Score (WDDS) and the seven-group young children's (6 to 23 months old) DDS (12,23,24) . All three systems have specific food groups for cereals and tubers, dairy products and legumes and nuts.…”
Section: Discussionmentioning
confidence: 99%
“…It is however important to note that our system differed from the WDDS in three specific ways: (i) we categorized VAFV and VCFV into two separate food groups; (ii) we did not categorize organ meats and flesh foods into two separate food groups; and (iii) we combined the MFP and egg categories into one food group due to the low intake values. Although Arimond et al showed that the nine-food-group system combined better performance and ease of implementation (12) , we selected to use eight food groups in our analysis to allow for 'food group' key nutrient homogeneity and practicality within our specific population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most frequently used individual indicators of dietary diversity, Minimum Dietary Diversity (MDD) for children 6-23 months of age and Women's Dietary Diversity, have been validated as proxy indicators of the nutrient adequacy of the diet (Arimond et al 2010;FAO and IRD 2014;WHO 2008). Many studies have shown positive associations between dietary diversity scores and nutritional outcomes (Ruel et al 2013b) and dietary diversity indicators are collected by large scale programs such as the Demographic and Health Surveys, Feed the Future, and CGIAR.…”
Section: Indicators For Diet Qualitymentioning
confidence: 99%
“…In resource-poor settings worldwide, low-quality, monotonous diets are common and the risk of micronutrient deficiencies is high (Arimond et al 2010;FAO 2013b). At the same time, global supply of food energy is dependent on only a small number of cultivated species and varieties (Barucha and Pretty 2010;FAO 2013a;Grivetti and Ogle 2000).…”
Section: Introductionmentioning
confidence: 99%